2020
DOI: 10.1039/d0nj03747h
|View full text |Cite
|
Sign up to set email alerts
|

A new V2O5–MoO3–TiO2–SO42−nanostructured aerogel catalyst for diesel DeNOxtechnology

Abstract: New V2O5-MoO3-TiO2-SO42- nanostructured aerogel system, containing V and Mo amounts representative of V2O5-MoO3/TiO2 commercial SCR catalyst, was developed via the one step sol gel method combined to supercritical drying approach...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…The authors concluded that the increase of Mn amount had a positive effect on the acidity of MnOx-CeO2/GR catalysts and contributes greatly to its high NO-SCR by NH3 activity. After sulfation of Mn-TiO2 catalyst, a new peak belonging to NH3-desorbed from strong acid sites, generated by sulfate groups, has appeared at high temperature ~ 500 °C [30,31]. It should be mentioned that the addition of cerium induces a decrease of the total acidity (mainly medium and strong ones) of the unsulfated and sulfated Mn based solids.…”
Section: Acidity and Reducibility Of Aerogel Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that the increase of Mn amount had a positive effect on the acidity of MnOx-CeO2/GR catalysts and contributes greatly to its high NO-SCR by NH3 activity. After sulfation of Mn-TiO2 catalyst, a new peak belonging to NH3-desorbed from strong acid sites, generated by sulfate groups, has appeared at high temperature ~ 500 °C [30,31]. It should be mentioned that the addition of cerium induces a decrease of the total acidity (mainly medium and strong ones) of the unsulfated and sulfated Mn based solids.…”
Section: Acidity and Reducibility Of Aerogel Catalystsmentioning
confidence: 99%
“…These species seem to be reduced at the same temperature range than manganese and affects its reducibility. The addition of sulfate completely hidden the reduction of other species, since, only one intense peak, corresponding to the reduction of sulfate groups, is detected at ~ 620 °C [30, 31,52] in the H2-TPR profiles of sulfated aerogel catalysts. It is worth noting that the intensity of the peak attributed to the reduction of SO4 2groups is higher in the case of Ce-Mn-TiO2-SO4 2catalyst compared to that of Mn-TiO2-SO4 2sample.…”
Section: Acidity and Reducibility Of Aerogel Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above discussion, and taking into account (i) the advantages of using the sol gel method for the preparation of highly active aerogel catalysts for the DeNOx process ( [45][46][47][48] [49]. It was revealed that the surface acidity plays an important role in the adsorption and activation of ammonia, especially at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Our particular interest in TiO 2 -supported MoO 3 is primarily derived from molybdenum oxide's ability to act as both a Lewis acid and base (29)(30)(31), as well as a redox-active promoter (32)(33)(34). Many important reactions such as hydrodesulfurization, selective oxidation, metathesis of olefins, and selective NOx reduction are catalyzed and or promoted by molybdenum oxides (2,(35)(36)(37)(38)(39)(40)(41)(42)(43). Further, titanium dioxide is often used as a reducible oxide support material which itself is capable of acid/base and redox chemistries.…”
mentioning
confidence: 99%